Impact of Rainfall and Temperature on Economic Growth in Angola, Botswana, Tanzania and Zimbabwe - Abel, Sanderson; Jeke, Leward (International Journal of Energy Economics and Policy, 2025)
Research indicates that temperature and precipitation have a big impact on economic growth due to greenhouse emission, especially in areas that depend heavily on agriculture. While extreme weather events like droughts or extreme heat can have a negative effect on production and impede economic development, optimal precipitation levels typically result in higher crop yields and economic activity. The purpose of this study is to econometrically test the effect of rainfall and temperature on economic growth in Angola, Botswana, Tanzania and Zimbabwe. The study specifically aims to respond to the following queries: Are rainfall and temperature important indicators of economic growth in Angola, Botswana, Tanzania and Zimbabwe? The results of the study established that rainfall has a negative effect in Angola only in the long run among the selected countries. In Botswana, Tanzania and Zimbabwe rainfall has no effect on economic growth in the long run. Whilst in the short run rainfall retains has a negative effect on economic growth in Angola and Botswana but positive relationship in Tanzania. On the other hand, result shows that temperature has positive impact in Angola and Tanzania with a unit increase in temperature increasing economic growth by 0.6088 and 0.6955 percent in Angola and Tanzania respectively in the long run. In the short run, temperature has been established to have a positive effect in Angola, Tanzania and Zimbabwe, reflecting that temperature rises have a beneficial effect in these countries. The results imply that climate related variables have an implication for economic growth.